Policy Change for Empowering MSMEs in The Covid-19 Pandemic Situation (Case Study of Increasing Competitiveness of Business Actors in Cianjur Regency) - Rohmah, Anisa Nur; Laksmono, Bambang Shergi (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
The COVID-19 pandemic has presented various problems and also has an impact on business actors, especially those engaged in the Micro, Small and Medium Enterprises (MSME) sector. They complained about the decline in sales, purchases, and even venture capital. The decline in MSME productivity, in a decrease in the Gross Domestic Product (GDP) in the regions, as well as the Human Development Index (IPM). Therefore, this study seeks to examine changes in MSME empowerment policies during the COVID-19 pandemic, in order to increase the competitiveness of business actors in Cianjur Regency. This study uses a qualitative approach with data collection through in-depth interviews, observation, and documentation studies. The data analysis technique was carried out through three stages, namely open coding, axial coding and selective coding. Research informants came from a) Department of Cooperatives, MSMEs, Trade and Industry of Cianjur Regency; b) Center for Integrated Services of SMEsCo in Cianjur Regency; c) Directorate of Domestic Trade, Ministry of Trade of the Republic of Indonesia; and d) SMEs in Cianjur Regency. The results of the study indicate that there are three aspects of MSME empowerment policies carried out by the Cianjur Regency Government, namely; a) Marketing, with a focus on online marketing through the creation of e-catalog and e-commerce applications in Cianjur Regency, as well as offline marketing through the application of Cianjur local government regulations and product diversification programs; b) Capital, which focuses on facilitating access to payments, and a revolving fund program with 0% interest.